"She finds you abhorrent" - The impact of emotional context information on the cortical processing of neutral faces in depression. - Iffland, Benjamin; Klein, Fabian; Schindler, Sebastian; Kley, Hanna; Neuner, Frank (Cognitive, Affective & Behavioral Neuroscience, 2021)
Depression is associated with abnormalities in patterns of information processing, particularly in the context of processing of interpersonal information. The present study was designed to investigate the differences in depressive individuals in cortical processing of facial stimuli when neutral faces were presented in a context that involved information about emotional valence as well as self-reference. In 21 depressive patients and 20 healthy controls, event-related potentials (ERPs) were recorded during the presentation of neutral facial expressions, which were accompanied by affective context information that was either self- or other-related. Across conditions, depressive patients showed larger mean P100 amplitudes than healthy controls. Furthermore, mean late positive potential (LPP) amplitudes of depressive patients were larger in response to faces in self-related than in other-related context. In addition, irrespective of self-reference, mean LPP responses of depressive patients to faces presented after socially threatening sentences were larger compared with faces presented after neutral sentences. Results regarding self-reference supported results of previous studies indicating larger mean amplitudes in self-related conditions. Findings suggest a general heightened initial responsiveness to emotional cues and a sustained emotion processing of socially threatening information in depressive patients.